2018
DOI: 10.1177/1048371318798829
|View full text |Cite
|
Sign up to set email alerts
|

Holistic Development and Music Education: Research for Educators and Community Stakeholders

Abstract: Many educators and parents remain unaware of the value of music and the arts beyond obvious, natural entertainment contexts and find it easy to devalue music and arts programing. This article presents a concise review of significant research that demonstrates strong correlations between the study of music and arts as academic disciplines that improve the development of literacy, language, and math skills while also providing a natural link to improved social and emotional competencies. The material is presente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 17 publications
0
5
0
1
Order By: Relevance
“…Activities such as improvisation, ensemble playing, group singing, and defining emotions within music listening examples are easy connections and natural links between general music learning and SEL. Rajalakshmi (2017) indicated that "music helps in fostering brain development, cognitive development, social-emotional learning and academic performance in healthy children and adolescents" (p. 4) and further demonstrated the value of music in our schools. For this article, successful students are defined as those who are able to focus their attention, set and monitor goals, recognize and resolve problems, make decisions, and use organizational skills (Frey, Fisher, & Smith, 2019) to achieve academic and personal objectives.…”
mentioning
confidence: 69%
See 1 more Smart Citation
“…Activities such as improvisation, ensemble playing, group singing, and defining emotions within music listening examples are easy connections and natural links between general music learning and SEL. Rajalakshmi (2017) indicated that "music helps in fostering brain development, cognitive development, social-emotional learning and academic performance in healthy children and adolescents" (p. 4) and further demonstrated the value of music in our schools. For this article, successful students are defined as those who are able to focus their attention, set and monitor goals, recognize and resolve problems, make decisions, and use organizational skills (Frey, Fisher, & Smith, 2019) to achieve academic and personal objectives.…”
mentioning
confidence: 69%
“…General music teachers often design learning opportunities that promote the development of appropriate student responses in challenging situations, such as rehearsal or general music-making settings. These student response opportunities are critical for the development of responsible decisionmaking skills (Varner, 2019). Many general music activities, like other performing arts endeavors, reinforce responsible decisionmaking skills when using and maintaining materials, equipment, and tools in work and performance spaces.…”
Section: Responsible Decisionmaking: Cognitive Regulationmentioning
confidence: 99%
“…Therefore, it becomes a good means for early childhood to learn in a fun way as the children will listen and focus their attention and practice their thinking skills. There is a strong correlation between learning music and art and improving literacy and mathematical skills [10]. Musical activities which emphasize song lyrics, rhymes, rhythmic patterns, constant beats, and dramatized stories through movement and musical instruments can expand and strengthen children's memory to help develop their linguistic skills.…”
Section: The Role Of Music For Childrens' Developmentmentioning
confidence: 99%
“…They believe that arts teachers should shape arts learning experiences to create emotionally safe spaces, provide opportunities to explore and express personal identity, and develop trusting relationships with students. Several arts educators have described what this looks like in particular arts disciplines (e.g., Jellison et al, 2017;Kay & Wolf, 2017;May & Robinson, 2016;Pereira & Marques-Pinto, 2018;Powers & Duffy, 2016;Usakli, 2018;Varner, 2019). Promoting and developing experience within SEL strategies during preservice arts teacher education could improve eventual experiences and outcomes in both K-12 arts and nonarts classrooms and enhance future collaborations with nonarts educators (Farrington & Shewfelt, 2020).…”
Section: Social Emotional Learning In Arts Teacher Educationmentioning
confidence: 99%